PROFILE OF PATIENTS SUBMITTED FROM PRIMARY HEALTH CARE IN THE MUNICIPALITY OF RIO DE JANEIRO TO THE AMBULATORY OF BENIGAL PATHOLOGY OF MASTOLOGY OF THE HOSPITAL UNIVERSITÁRIO GAFFRÉE E GUINLE (HUGG): A CROSS-SECTIONAL STUDY - Prado, Julia Dias do; Toledo, Michelle Gomes Soares; Almeida, Sandra Maria Garcia de; Amaral, Luiz Fernando Pinho do; Luna, Cristiano Rodrigues de (Mastology, 2020)
Introduction: In the Brazilian Unified Health System (Sistema Único de Saúde – SUS), since 2012, referrals to the municipal outpatient network are carried out through the National Regulation System (Sistema Nacional de Regulação – SISREG). The system works online and, daily, doctors in the family health strategy of Primary Care request consultations and tests that, after being approved, are scheduled by the units that provide the service. The objective of SISREG is to optimize resources and to improve the flow of calls. Calls are classified according to priority criteria containing an appointment period of 30 to 180 days. The Mastology outpatient clinic at HUGG offers SISREG 4 vacancies per week for consultation on benign bre-ast pathology. Objective: To evaluate the profile of patients referred to the Mastology Service at HUGG and their role in the context of SUS. Method: The medical records of patients referred through SISREG to the Mastology outpatient clinic of HUGG were carried out from January to December 2019. Results: 97 patients were referred, but only 90 of them atten-ded the consultation. 7% of the patients had no indication for specialized monitoring, 48% of the patients already had a previous biopsy, 15% had a biopsy, 30% had surgery indication, and 19% had a suspected or confirmed lesion for breast cancer. Of the patients with a family history record, 20% had an indication for genetic study for research of hereditary breast cancer. Of those with registered BMI, more than 60% were overweight or obese. The minority regularly drank alco-holic beverages (2%) or had a history of smoking (30%). A quarter of the patients did regular physical activity. The average time between the request date and the day of the consultation was 67 days, the majority of which was spent between the date of approval in the request unit until the appointment at HUGG. Priority time was respected 75% of the time. 40% of the vacancies offered were not filled. Conclusion: A good part of the population served is overweight, sedentary, and a significant portion has a positive family history for breast cancer. In addition, the offer in consultation for benign breast pathology seems excessive, and for this reason, in 2020, we decided to open vacancies for breast biopsy, aiming at better matching supply and demand, thus seeking the best assistance to the population of Rio de Janeiro.